Social Rehabilitation, Reintegration of Substance abusers and Sustainable Development Goals: Assessing attitudes of college students of Delhi NCR, India - Gautam, Upma; Tewari, Deeksha Bajpai; Das, Priya; Jaiswal, Vaishnavi; Mishra, Ankita; Verma, Kanishka; Marjara, Kriti (European Journal of Sustainable Development, 2025)
Background: Effective and sustainable drug policy for youth in alignment with Sustainable Development Goal 3.5 encompasses two primary approaches: addressing the etiological factors and consequences of substance abuse and enhancing the health outcomes of young substance users while expanding rehabilitation opportunities. Aims and objective: Effective social reintegration of young substance abusers requires understanding stigma among peers regarding the possibility and effectiveness of rehabilitation. Methods: A self-designed questionnaire containing 28 Questions was administered to 453 (n=453) college students in Delhi NCR. Of the total 453 respondents, 281 (62.03 percent) were male and 172 (37.97 percent) female students. Results: The mean attitude score for the substance abuse and abuser subscale was 22.99 (min = 11.50, max = 29). The mean score for the impropriety of substance abuse subscale was 11.139 (min = 3, max = 29). The mean score for the legal and policy response subscale was 23.10 (min = 10.29, max = 32.71). The mean score for the rehabilitation and reintegration subscale was 33.33 (min = 25, max = 44.88). More male respondents (75.44%) than female respondents (69.18%) believed substance abuse is a habit, not a disorder. Conclusion: Out of all social-demographic factors, none significantly impacted the average attitude score on substance abuse and the abuser. However, average attitude scores on the impropriety of substance abuse subscale varied significantly across the course and year of study categories. Average attitude scores on the rehabilitation and reintegration subscale varied significantly across the gender and categories of respondents with drug users among their known groups. An integrated cohesive approach where various stakeholders’ contributions are mutually reinforcing and holistic in addressing the social issue of substance abuse among college students needs to be adopted. Keywords: Rehabilitation, Social Reintegration, Institutional Interventions, College Students, Substance Abuse.